Long-term outcomes and patient profiles following intensity-modulated radio-chemotherapy for nasopharyngeal cancer in a nonendemic region - Dragan, Tatiana; Chiairi, Ibrahim; Salmon, Maurine; Lalami, Yassine; Digonnet, Antoine; Lipski, Samuel; Van Gestel, Dirk (Frontiers in Oncology, 2026)
IntroductionNasopharyngeal carcinoma (NPC) is rare in non-endemic regions but poses unique clinical challenges, especially among ethnically diverse populations. This study aimed to evaluate the characteristics, treatment outcomes, and toxicity profiles of NPC patients treated with definitive intensity-modulated radio-chemotherapy (IMRT-CRT) in a non-endemic European center.MethodsWe conducted a retrospective analysis of 82 consecutive patients with histologically confirmed NPC treated at Institut Jules Bordet between 2012 and 2024. Patient, tumor, treatment characteristics, survival outcomes, and treatment-related toxicity were evaluated. Survival endpoints were calculated using the Kaplan-Meier method and multivariate Cox regression.ResultsThe median follow-up was 35 months. Most patients were male (77%), of North African descent (66%), and had non-keratinizing carcinoma (96%). Advanced disease (stage III/IV) was present in 72%, and 78% of tested tumors were EBV-positive. Induction chemotherapy (ICT) and concurrent chemotherapy (CCT) were administered in 32% of patients. At 5 years, actuarial estimates for overall survival (OS), progression-free survival (PFS), locoregional disease-free survival (LRDFS), recurrence-free survival (RFS), and distant disease-free survival (DFS) were 73%, 79%, 86%, 87%, and 87%, respectively. Higher T stage, treatment-related weight loss, positive nodal findings on 3-month FDG-PET-CT, and disease recurrence were associated with worse OS. Acute and late toxicities were generally manageable; however, xerostomia, hypothyroidism, ototoxicity, and weight loss were prevalent.ConclusionsDespite being conducted in a non-endemic region, this study revealed NPC characteristics and outcomes resembling those in endemic populations, likely due to patient demographics. Early metabolic response and nutritional status emerged as critical prognostic factors, highlighting the need for individualized treatment and supportive care strategies in NPC management.